2010
DOI: 10.1128/mcb.01345-09
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Rap1GAP in Human Tumor Cells Alters Cell/Matrix and Cell/Cell Adhesion

Abstract: Rap1GAP expression is decreased in human tumors. The significance of its downregulation is unknown. We show that Rap1GAP expression is decreased in primary colorectal carcinomas. To elucidate the advantages conferred on tumor cells by loss of Rap1GAP, Rap1GAP expression was silenced in human colon carcinoma cells. Suppressing Rap1GAP induced profound alterations in cell adhesion. Rap1GAP-depleted cells exhibited defects in cell/cell adhesion that included an aberrant distribution of adherens junction proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…7A) and previous studies suggest Rap1GAP and its family members Rap1GAPII, Spa1/SIPA1, and E6TP1 possess tumor metastasis suppressor activities. Rap1GAP protein levels are decreased in several types of cancer, including pancreatic adenocarcinoma (55), papillary thyroid carcinoma (56,57), colorectal carcinoma (58), and melanoma (59). The implication of Rap1GAP as a tumor suppressor was largely deduced based upon experimental results using forced overexpression of full-length Rap1GAP (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…7A) and previous studies suggest Rap1GAP and its family members Rap1GAPII, Spa1/SIPA1, and E6TP1 possess tumor metastasis suppressor activities. Rap1GAP protein levels are decreased in several types of cancer, including pancreatic adenocarcinoma (55), papillary thyroid carcinoma (56,57), colorectal carcinoma (58), and melanoma (59). The implication of Rap1GAP as a tumor suppressor was largely deduced based upon experimental results using forced overexpression of full-length Rap1GAP (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…S1B), indicating that the activity of Rap1 and Rap2 is regulated in close proximity to the plasma membrane by Rap1 GAPs. Because activation of Rap signaling, Rac signaling and/or ezrin signaling, has been shown to impair cell-cell adhesion by destabilizing E-cadherin at the cell-cell junctions (Lozano et al, 2008;Pujuguet et al, 2003;Tsygankova et al, 2010) and because reduced accumulation of E-cadherin at the cell-cell junctions was observed in the Slp2-a-KD cells (supplementary material Fig. S4A), it is highly possible that activation of these signals facilitates cell spreading by disrupting cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Rap1GAP is decreased in tumors of the pancreas, skin, thyroid and colon. [1][2][3][4][5][6] Rap1GAP expression is further decreased in invasive compared to benign lesions, suggesting that depletion of Rap1GAP enhances tumor progression. 1,2,4,5 The advantages conferred to tumor cells by the downregulation of Rap1GAP are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 We previously reported that silencing Rap1GAP expression in human colon cancer cells impaired cell-cell adhesion and enhanced spreading on collagen. 6 The weakening of cell-cell contacts together with alterations in matrix adhesion are hallmarks of tumor progression. These data suggest that loss of Rap1GAP endows cells with the ability to disseminate and provide a potential rationale for the progressive downregulation of Rap1GAP in human tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation